Pengaruh DAK, DAU, PAD, DBH, UMR & Angkatan Kerja Terhadap Belanja Modal Di Provinsi Jawa Tengah - Lusmino Basia; Afriyanti Afriyanti; Mahrus Lutfi Adi Kurniawan (Jurnal Ilmiah Raflesia Akuntansi, 2025)
— This study aims to analyze the effect of Special Allocation Fund (DAK), General Allocation Fund (DAU), Regional Original Income (PAD), Revenue Sharing Fund (DBH), Regional Minimum Wage (UMR), and Labor Force on Capital Expenditure in Central Java Province during the period 2016-2021. The main focus of this study is to evaluate how these variables affect the allocation and use of Capital Expenditure which in turn has the potential to increase the capacity and quality of regional infrastructure and support economic growth. Based on the results of the analysis, there is a significant negative effect of the variables GDP-1, GDP-2, and GDP-3 on economic growth in the short term. Direct investment has an insignificant effect on GDP in the short term. Although investment is important, the risks associated with investment, such as market risk, liquidation, interest rates, and politics, can negatively affect investment returns if not managed properly. Remittances show a significant effect on GDP in the short and long term. Remittances can increase people's income, especially for migrant worker families, which in turn can reduce poverty. However, if not managed properly, remittances can also have a negative impact. Interest rates do not show a significant impact on GDP in the short term, high interest rates can dampen consumption as borrowing becomes more expensive, which can negatively affect the economy.